Capability approach and determinants of out-of-pocket spending on health in households in Argentina - Basso, Martín Alejandro (2024)
This paper analyzes the out-of-pocket spending of households in Argentina within the framework of the capabilities approach. For this, we worked with the National Household Expenditure Survey, in the period 2017-2018 using a Tobit model as a statistical methodology. It was found that out-of-pocket spending on health as a proportion of household spending increases by 0.0104 with an increase of one percentage point in income. Out-of-pocket spending on health is also affected by the number of members over 65 years of age and under 14 years of age, as well as the educational climate and whether or not the head of household has medical coverage. Finally, there were differences between the different geographical regions of the country.